Determinants of free serum valproate concentration: A prospective study in patients on divalproex sodium monotherapy. (July 2018) - Nasreddine, Wassim; Dirani, Maya; Atweh, Samir; Makki, Achraf; Beydoun, Ahmad
Highlights: VPA free fraction increases linearly with a rise in total VPA concentration. A quadratic non-linear equation correlates total and free VPA concentrations. VPA dose should be increased in small increments after total VPA level of 60 μg/mL. Abstract: Purpose: To evaluate variables affecting the valproate (VPA) free fraction and develop an equation for computing free VPA concentration from total VPA concentration. Methods: Trough total and free VPA concentrations were collected from patients who participated in a prospective VPA monotherapy trial. All available paired data of trough total and free VPA concentrations were included. Significant variables from the univariate analysis were evaluated in a multivariate model. Results: A total of 902 concomitant total and free VPA concentrations were available. Multivariate analysis showed that total VPA concentration, age and gender were significantly associated with VPA free fraction. However, the effect size of total VPA concentration was substantially higher than that of gender and age. VPA free fraction remained stable at around 10% for total VPA concentration between 20 and 60 μg/mL with subsequent linear increases for higher concentration. A scatter plot correlating total and free VPA concentrations showed that a quadratic equation best fitted the data, accounting for 88% of the free VPA concentration variance. Conclusions: An increase in the total VPA concentration results in corresponding linear and non-linear rise in the VPA free fraction and free VPA concentration, respectively. The total daily dose of VPA should be increased in smaller increments whenever a total VPA concentration of 60 μg/mL is reached. When drug monitoring is needed, we recommend measuring the free VPA concentration. If this test is unavailable, and for patients with normal albumin levels, it can be predicted from the total VPA concentration using the generated equation.